Compound odontoma in the anterior region of the mandible: clinical case report (Research, Society and Development, 2021)
Odontomas are classified as a malformation where epithelial and mesenchymal cells have the ability to produce dental tissues such as enamel and dentin. Of unknown etiology, they are often associated with failure of eruption of permanent teeth and / or late impaction or exfoliation of deciduous teeth. Surgical removal is the therapeutic option of choice for the treatment of this condition, since its presence can cause some intercurrences as root resorptions of the neighboring teeth. The objective of this case report is to describe a surgical approach for the removal of a composite odontoma in the anterior region of the mandible, where after a 5-year postoperative follow-up, it was possible to observe in radiographic and tomographic analyses, small images of radiopaque characteristic compatible with recurrence tumor, hypercalcification or remnant of the lesion.